METHODS OF DETERMINING THE HIDDEN ECONOMY AND WAYS OF ITS REFLECTION IN GROSS DOMESTIC PRODUCT - Mavlyanov Muzaffar (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
In this article, the scale of development of the hidden economy and the reasons for its growth are analyzed, the methods of their detection and its impact on the gross domestic product are theoretically studied, and in this context, scientific proposals and recommendations for research work are developed.